(untitled) (Research, Society and Development, 2022)
Red mud is the main by-product from bauxite processing, known worldwide as the Bayer process. Its production is growing all over the world, with a highlight in Brazil, the states of Pará and Minas Gerais. However, due to the chemical characteristics of this waste, as well as the high amount that is generated, environmental agencies are increasingly demanding that the generating sources create methods for reusing this waste, in order to collaborate with the reverse logistics of this material. In this sense, several studies have been carried out aiming at the reuse of red mud for the production of new materials, among which the light aggregate stands out, which can be used in the civil construction sector, which is one of the largest consumer sources of this type of product. Based on this bias, the present study evaluated, based on a systematic literature review, the potential application of red mud in the manufacture of lightweight aggregates. Important data such as: chemical composition; density; granulometry; mechanical resistance; water absorption; sintering temperature and application in concrete were analyzed and compared with the relevant standards on the subject. The results are encouraging, proving that in all parameters analyzed, the recycled aggregates produced met the normative standards currently required, having a performance similar to that of conventional aggregates. Therefore, it was concluded that red mud has technical feasibility for the manufacture of light aggregates, confirming the potential of reverse tailings logistics for this purpose.